LIFESTYLE ACCORDING TO AYURVEDA IN COVID-19 PANDEMIC - kamble, Krutika; Dhavale, Suvarna (International Journal of Research -GRANTHAALAYAH, 2020)
Background: The current covid-19 Pandemic situation has affected many lives, their health and well-being. This pandemic situation undoubtedly contribute to sudden change in daily routine like social distancing, isolation leads to emotional distress and increased risk for psychiatric illness. Day by day increase in number of patients of covid-19 put all of us in great fear, stress, uncertainty about life, loss of will power, loss of positivity about life. Ayurveda does not only deal with physical wellness but mental wellness also. Ayurveda, the science of life dealing with maintenance of everyones health and eliminating rogas From body. Ayurveda will definitely help us out from this worst situation by some easy lifestyle hacks. Ayurveda has already gifted us with lots of easy going daily routine Concepts for betterment of life. Now it is the time to when we should understand importance of Ayurveda and pick some lifestyle hacks according to Ayurveda such as Dincharya, Ratricharya, Ritucharya, Ahara, Rasayana, Yoga, pranayama etc. Objectives: An overview of Dinacharya and Ahara in covid-19 pandemic situation for physical and mental health improvement.